Kontribusi Generasi Muda Dalam Perkembangan Pemberdayaan Hidroponik: Kontribusi Generasi Muda Dalam Perkembangan Pemberdayaan Hidroponik - Wasesa , Rayjaka; Rozaki, Zuhud; Wulandari , Retno; Distrianada, Ridho Ikbar (Universitas Muhammadiyah Yogyakarta, 2024)
Indonesia is one of the countries that rely on the agricultural sector as its advantage. However, the need for good quality and human resources has decreased in recent years, especially in the agricultural sector, which will affect the contribution of the young agricultural workforce/young generation to the success of agriculture in Indonesia. Hydroponics is agricultural cultivation without the use of soil media, so hydroponics is an agricultural activity carried out using water as a medium to replace soil.The purpose of this paper is to find out about the contribution of the younger generation in today's agricultural field, especially in hydroponic farming. the search method for this paper uses the journal search method with the Google Scholar web. the result of this paper is to find out detailed details about the contribution of hydroponic farming with references in several villages and schools. This paper has many benefits so that we can know more up-to-date information, so that it can be a reference or material to start hydroponic farming properly.